(untitled) (Texas Journal of Medical Science, 2026)
The article deals with the study the histotopographic changes in ovarian tissue of 6- month-old children. The ovaries of 6-month-old children who died of pneumonia were studied histologically and histochemically. The results show that the primordial eggs of a 6-month-old child are located in the middle zone of the cortex, have different sizes, some are atretized, others are vacuolized, and granulose and teka cells are activated randomly. they are localized and proliferate in interstitial tissue. Histochemically, it was found that collagen fibers stained with picrofuxin appeared around blood vessels between primordial eggs, acid glycosaminglycans stained with Altian blue are few due to the density of the tissue of the cortical layer and diffusely distributed due to the rarity of the cerebral layer. the tissue is swollen and myxmatous. At the age of 6 months, it is determined that the ovarian medulla is insufficiently developed, the blood vessels are small, the wall cells are hyperchromic due to lack of differentiation, and the cells and fibrous structures in the intermediate connective tissue are few and incomplete